THE INVESTIGATION ORE DEPOSIT OF RADIOISOTOPE ELEMENT WITHIN THE MINING SUBSTANCE IN THE WEST TIMOR ISLAND NUSA TENGGARA TIMUR - Pasangka, Bartholomeus; -, Prayoto; Brotopuspito, Kirbani Sri; -, Waluyo (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2007)
These research inspect the distribution and the accumulation shape of ore depo-sit anomaly of radioisotope element within the mining substance at Sub-district of Amara-si and East – Middle Kupang West Timor Island. The aims of the research: 1) to localize the distribution wide of radioisotope element within the mining substance, 2) to stake out the target reconstruction or shape of accumulation anomaly ore deposit of radioisotope e-lement within the mining substance, 3) to decide counts range of nuclear radiation and thermal counts in the center region of radioisotope source in the West Timor Island. The methods of research consist of: observation, survey, modeling, analysis, and interpretation. Procedures of research including: 1) to observe for determination the po-tential region and grid plot, 2) to calibrate equipment, 3) to measure background count in around of survey location, 4) to measure nuclear radiation and thermal count in the sur-vey location, 5) to correct field count with background count, 6) two and three dimensional characteristic curve of radiation and thermal count plot, contour, contour slice, and distri-bution profile curve of ore deposit anomaly of radioisotope in the mining substance al-so plot, 7) to determine the depth of ore deposit of radioisotope element within the mi-ning substance and radiation power, 8) to calculate radiation intensity for modeling of tar-get reconstruction, 9) to stake out modeling and target reconstruction of ore deposit of ra-dioisotope in the mining substance, 10) interpretation and conclusion. The results of the research: radiation power to determine radiation intensity is 1183911,452 w. Based on characteristic curve, contour, profile curve, and modeling of o-re deposit anomaly (target reconstruction) of radioisotope element within the mining subs-tance, can be proposed that the wide of ore deposit distribution of radioisotope element in rock mineral 1.5 kilometers x 2.0 kilometers, and the wide of ore deposit center region 200 meters x 300 meters. The shape of ore deposit anomaly of radioisotope element wi-thin the mining substance resemble of oval ball vertically with diameters ± 54 meters hori-zontal, and ± 100 meters vertical on the average depth 22 meters, and the shape on abo-ve surface is dented. The range thermal and radiation counts of radioisotope element in the mining substance revolve between 20.3o C to 50.7o C and 9 counts per minute to 117 counts per minute.